Pendidikan Islam di Era Abu Ja’far Al-Mansur: Dari Politik Menuju Keilmuan - Salsabila Khairani; Fatimah Al Jahra; Mahfud Ifendi (CV Kalimasada Group, 2025)
This article aims to examine the strategic role of Caliph Abu Ja'far al-Mansur in shaping the foundations of Islamic education during the early Abbasid dynasty. The focus of this research is to explore how the political stability built by al-Mansur led to the advancement of Islamic science and education. This research uses a descriptive qualitative method with a historical approach, through a literature study of historical documents, biographies of figures, and relevant scientific literature. Data collection techniques were conducted through literature review, and the data were analyzed narratively and contextually. The results showed that Abu Ja'far al-Mansur played an important role in strengthening the Islamic education system through the development of the city of Baghdad as a center of science, empowering traditional institutions such as mosques, kuttabs, and halaqahs, as well as initiating a movement to translate foreign works into Arabic. He also opened up space for the participation of non-Arabs (mawali) in intellectual activities and began to build an administrative system that supported education and learning. This finding confirms that the era of al-Mansur was the initial period of the formation of an Islamic education system that was inclusive, dynamic, and became the basis for scientific development in the following period.